Numerical analysis of the pulsating heat source effects in a tumor tissue. (March 2021) - Andreozzi, Assunta; Brunese, Luca; Iasiello, Marcello; Tucci, Claudio; Vanoli, Giuseppe Peter
Abstract: Background and objectives: Hyperthermia treatment is nowadays recognized as the fourth additional cancer therapy technique following surgery, chemotherapy, and radiation; it is a minimally or non-invasive technique which involves fewer complications, a shorter hospital stay, and fewer costs. In this paper, pulsating heat effects on heat transfer in a tumor tissue under hyperthermia are analyzed. The objective of the paper is to find and quantify the advantages of pulsatile heat protocols under different periodical heating schemes and for different tissue morphologies. Methods: The tumor tissue is modeled as a porous sphere made up of a solid phase (tissue, interstitial space, etc.) and a fluid phase (blood). A Local Thermal Non-Equilibrium (LTNE) model is employed to consider the local temperature difference between the two phases. Governing equations with the appropriate boundary conditions are solved with the finite-element code COMSOL Multiphysics®. The pulsating effect is modeled with references to a cosine function with different frequencies, and such different heating protocols are compared at equal delivered energy, i. e. different heating times at equal maximum power. Results: Different tissue properties in terms of blood vessels sizes and blood volume fraction in tissue (porosity) are investigated. The results are shown in terms of tissue temperature and percentage of necrotic tissue obtained. The most powerful result achieved using a pulsating heat source instead of a constant one is the decreasing of maximum temperature in any considered case, even reaching about 30% lower maximum temperatures. Furthermore, the evaluation of tissue damage at the end of treatment shows that pulsating heat allows to necrotize the same tumoral tissue area of the non-pulsating heat source. Conclusions: Modeling pulsating heat protocols in thermal ablation under different periodical heating schemes and considering different tissues morphologies in a tumor tissue highlights how the application of pulsating heat sources allows to avoid high temperature peaks, and simultaneously to ablate the same tumoral area obtained with a non-pulsating heat source. This is a powerful result to improve medical protocols and devices in thermal ablation of tumors.